Evaluation of eight maize varieties in a diallel design with an analysis of the means of hybrids, their advanced generations and inbreds - Pinto, Luiz Roberto Martins; Silva, José Carlos; Sediyama, Carlos Sigueyuki; Silva, Martinho de Almeida e (Pesquisa Agropecuaria Brasileira, 2014)
Eight corn varieties, with great genetic diversity among them, were studied in a diallel cross system in order to evaluate their breeding potential. The means of the varieties, their hybrids and advanced generations were analyzed using the Gardner & Eberhart (1966) model. With the genetic constants estimated it was possible to estimate the mean grain yield for several types of populations (double hybrids, triple hybrids, synthetic varieties, etc). The best varieties were: Tuxpeño La Posta, Eto Blanco, Centralmex and Pérola Piracicaba.